PENGARUH PERPUTARAN MODAL KERJA DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH PERUSAHAAN MAKANAN DAN MINUMAN - Kartika Rachmadanti; Dian Hakip Nurdiyansyah (Jurnal Apresiasi Ekonomi, 2022)
This study aims to determine the effect of working capital turnover and operating costs on net income (Case Study of Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange 2016-2020). This study uses a quantitative approach. The population in this study includes Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange 2016-2020. The sample was determined by purposive sampling technique. The data analysis method used is multiple linear regression. The results of this study indicate that (1) Working Capital Turnover has no effect on net income. This is indicated by the regression coefficient value of 0.790 and the resulting significance value is smaller than the required one, namely 0.434 < 0.05. (3) The value of R square is 0.735. This means that the independent variable is able to explain the dependent variable of 73.5%. And the remaining 26.5% is explained by other variables not examined in this study